Effects of methane addition on laminar flame characteristics of premixed blast furnace gas/air mixtures. (15th October 2021) - Zheng, Weilin; Pang, Liyao; Liu, Yu; Xie, Fan; Zeng, Wen
Highlights: We focus on laminar flame characteristics of BFG with various CH4 additions. CH4 addition exhibits opposite effects on SL and Lb at ϕ = 0.8–1.2 and ϕ = 1.4. Thermal effect plays a major role at ϕ = 0.8–1.2 instead of chemical effect at ϕ = 1.4. R38 and R52 are the main chain branching and chain termination reactions. OH and H concentrations evidently increase with methane addition. Abstract: As a typical low heating value fuel, blast furnace gas (BFG) is used as an alternative fuel for gas turbine combustion. Due to its high concentration of inert gas components, natural gas is usually added to improve ignition and stable combustion in the combustion chamber. In this paper, laminar flame characteristics of BFG/CH4 /air mixtures were investigated using constant volume combustion chamber and CHEMKIN package using the Gri-Mech 3.0 model. Experiments and numerical simulations were conducted at an elevated pressure and temperature of 0.2 MPa and 453 K, equivalence ratios of 0.8–1.4, and mixing ratios of methane of 0, 5, 10, 15%. The results show that the laminar burning velocity decreases rapidly from 24.19 cm/s to 13.90 cm/s at ϕ = 1.4 with the increase of methane addition from 0% to 15%, but obviously increases from 16.49 cm/s to 28.68 cm/s at ϕ = 0.8, from 21.05 cm/s to 35.65 cm/s at ϕ = 1.0, from 23.52 cm/s to 32.09 cm/s at ϕ = 1.2 with the increase of methane addition from 0% to 15%. Meanwhile, methane addition has an opposite effect on the Markstein length at ϕ = 0.8–1.2 and ϕ = 1.4. The thermal, transport and chemical effects were examined, exhibiting a major role of the thermal effect in the range of ϕ = 0.8–1.2 and a significant contribution of the chemical effect at ϕ = 1.4 to the laminar flame propagation of BFG/CH4 /air mixtures. Further sensitivity analysis shows that R38 (H + O2 ↔ O + OH) and R52 (H + CH3 (+M) ↔ CH4 (+M)) are the main chain branching and chain termination reactions, respectively. Analysis on flame structure indicates that concentrations free radicals, especially OH and H evidently increase with methane addition. The maximum mole fraction of OH increases almost linearly from 1.02 × 10 - 3 to 3.82 × 10 - 3 with the increase of methane addition from 0% to 15%. The maximum mole fraction of H increases with a lower gradient than that of OH from 1.31 × 10 - 3 to 2.89 × 10 - 3 with the increase of methane addition from 0% to 15%.